A comparative study of single-loop VSG and multi-loop VSG. (August 2022) - Han, Feng; Zhang, Xing; Guo, Zixuan; Wang, Jilei; Fu, Xinxin; Gao, Bo
Abstract: The large-scale access of renewable energy generation has caused weak grid and a series of instability issues. Virtual synchronous generators (VSG), which can support the voltage and frequency, are gaining increasing applications. At present, there are two main types of VSG. One is single-loop VSG containing only a power control loop. The other is multi-loop VSG containing not only a power control loop, but also a voltage inner loop and a current inner loop. Although both VSGs exhibit the external characteristics of synchronous generators, there are still some differences between them. However, there are few studies on this issue, which makes it difficult to choose which type VSG to use in practical application. This paper analyzes the differences between the two VSGs in terms of broadband stability and current distortion suppression capabilities, so as to provide a reference for related applications.